Utilization Of Waste Selection Of KOI Fish Cultivation In Improving The Food Security Of The Community (Fullowers) In The Village Of Kondangjajar, Pangandaran Regency - Kosasih Adi Saputra; Defri Mulyana; Randy Fadillah Gustaman; Thaufan Abiyuna (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Covid-19 is an epidemic that has a huge impact on people's lives around the world. One of the sectors that the government is currently paying attention to is the food security of the community, which is feared to be affected by the COVID-19 pandemic. Academics in universities have very vital roles and responsibilities in solving these problems. The main object of this community service focuses on how to utilize koi fish farming waste so that it can be utilized by the community in supporting food security in the midst of the current covid-19 pandemic. Koi fish culture waste here is fish seed that does not pass the selection of koi fish quality. So far, in traditional koi cultivation, koi fish seeds that do not pass the selection will be destroyed. In fact, the number of koi fish seeds that did not pass the selection was an average of 80% of the total fish seeds in one spawning. The community service locations that become partners are 2 (two) fishery groups in the Kondangjajajar Village area, Kec. Cijulang, Pangandaran Regency. It is reasonable that the utilization of koi fish selection waste in the cultivation system in that place is not effective and needs assistance to change to a more effective direction.